2019
DOI: 10.14744/tjtes.2019.47382
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of conservative approach in right colon diverticulitis

Abstract: BACKGROUND: Approximately 10%-25% of patients with colon diverticular disease experience colonic diverticulitis during their lives. Right-sided diverticulosis is a rare condition in Western countries, but it is common among Asian countries. The aim of this study was to evaluate the clinical and treatment outcomes in our patients with right colon diverticulitis. METHODS: Demographic and clinical data of 22 patients with a diagnosis of cecum and right-sided colon diverticulitis between 2014 and 2017 were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…As a treatment option, non-operative methods should be preferred, in cases without diffuse peritonitis although differentiating benign and malignant cases pre-operatively is often difficult [123]. Surgical treatment is usually used in the treatment of complicated cases [116,124,125]. Resection of the inflamed colon with primary anastomosis can be performed by laparoscopy in experienced centers [126].…”
Section: Should Laparoscopic Resection Be Preferred To Open Resection In Patients With Diffuse Peritonitis Due To Perforated Diverticulitmentioning
confidence: 99%
“…As a treatment option, non-operative methods should be preferred, in cases without diffuse peritonitis although differentiating benign and malignant cases pre-operatively is often difficult [123]. Surgical treatment is usually used in the treatment of complicated cases [116,124,125]. Resection of the inflamed colon with primary anastomosis can be performed by laparoscopy in experienced centers [126].…”
Section: Should Laparoscopic Resection Be Preferred To Open Resection In Patients With Diffuse Peritonitis Due To Perforated Diverticulitmentioning
confidence: 99%
“…As a treatment option, non-operative methods should be preferred in cases without diffuse peritonitis, although differentiating benign and malignant cases pre-operatively is often difficult [ 164 ]. Surgical treatment is usually used in the management of complicated cases [ 165 , 166 ]. Resection of the inflamed colon with primary anastomosis may be performed laparoscopically in experienced centers [ 167 ].…”
Section: Acute Right Colonic Diverticulitismentioning
confidence: 99%
“…Although both our own study and previous studies [14,21] showed that conservative treatment of acute RCD was safe and effective, it remains unclear whether or not patients with uncomplicated and complicated RCD are both recommended for the same treatment. All patients were, therefore, divided into either a uncomplicated group or a complicated group, according to their radiological imaging features and clinical assessment.…”
Section: Resultsmentioning
confidence: 73%
“…Conservative treatment with intravenous antibiotics and bowel rest is usually recommended for the management of acute uncomplicated RCD in Asia [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%